THE EFFECT OF CURRENT RATIO, DEBT RATIO AND RETURN ON ASSETS ON FINANCIAL DISTRESS ON MANUFACTURING COMPANIES LISTED ON IDX FOR THE 2017-2019 PERIOD - Poniwatie, Asmie; Istanti, Enny; Prasta, Vamilia Indah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The problem of fluctuating financial conditions due to the impact of the MEA free market, if allowed to drag on can result in bankruptcy. Therefore, it is very important to have research related to financial distress, to find out these conditions can be seen and measured through financial statements using financial ratios, namely Current Ratio, Debt Ratio and Return on Assets. The sample of this study amounted to 33 company financial statement data obtained from 2017-2019. This research is based on a quantitative approach using statistical testing of the hypothesis using multiple linear regression with the help of SPSS version 23 program. The results of this study show that partially the current ratio variable, debt ratio and return on assets have a significant effect on financial distress. Simultaneously, the variable current ratio, debt ratio and return on assets have a significant effect on financial distress. And the current ratio variable has a dominant effect on financial distress.